Mineralogy of the lower part of the upper zone, eastern Bushveld Complex : implications for ore-forming processes - Von Gruenewaldt, G. (Gerhard), 1942- (University of Pretoria, 2025)
Thesis (PhD (Geology))--University of Pretoria, 1991.